2015
DOI: 10.1016/j.sbspro.2015.07.154
|View full text |Cite
|
Sign up to set email alerts
|

The Model for Introduction of Gamification into E-learning in Higher Education

Abstract: The following paper presents the model for introduction of gamification into the field of e-learning in higher education. Concepts and differences between techniques and methods of game-mechanics and game dynamics are explained. With proper integration of gamification in the field of e-learning into higher education, a positive impact on the learning process can be achieved, such as higher satisfaction, motivation and greater engagement of students. The importance of clearly defined objectives, rules, techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
165
0
35

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(200 citation statements)
references
References 33 publications
0
165
0
35
Order By: Relevance
“…More recently, it has also been suggested that players of commercial games are developing problem solving and literacy skills (Urh et al, 2015). It means that the good commercial games have good learning principles that provide opportunities for gamers to engage and improve their skills during gameplay.…”
Section: Educational Gamesmentioning
confidence: 99%
“…More recently, it has also been suggested that players of commercial games are developing problem solving and literacy skills (Urh et al, 2015). It means that the good commercial games have good learning principles that provide opportunities for gamers to engage and improve their skills during gameplay.…”
Section: Educational Gamesmentioning
confidence: 99%
“…At the same time, it contributes to higher public status of an institution of higher education and development of digital skills of students, teachers and administrative staff. Urh et al [15] write that "e-learning is being introduced as a fundamental part of the student learning experience in higher education". Divjak and Begičević [16] state that e-learning "supports skills needed in knowledge-based society and includes different teaching methods".…”
Section: State Of the Artmentioning
confidence: 99%
“…Es indudable que la investigación en gamificación está en sus inicios (Urh, Vukovic, Jereb y Pintar, 2015); y, además, existen voces que recuerdan la dificultad que supone implementar metodologías gamificadas (Barragán, 2015) que tienen el riesgo de fracasar si no están bien planificadas o ligadas a objetivos didácticos concretos, y que, además, gamificar requiere un gran consumo de tiempo por parte de los docentes ya que ha de hacerse para un grupo de clase específico (Brigham, 2015). Sin embargo, sus beneficios quedan demostrados en experiencias concretas que se han llevado a cabo y que exponen como resultado que una buena implementación de la gamificación repercute positivamente en el proceso de enseñanza-aprendizaje (Moreno et al, 2014;Torres, 2016;Tauler;.…”
Section: Discusión Y Conclusionesunclassified